Perceived quality of internships and employability perceptions: the mediating role of career-entry worries. Issue 4 (12th February 2021) - Ebner, Katharina; Soucek, Roman; Selenko, Eva
Abstract : Purpose: This study illuminates the assumption that internships facilitate labor market entry and answers the question of why internships have a positive effect on students' self-perceived employability. It is assumed that internships enable more positive employability perceptions by reducing career-entry worries – the worries of not finding a suitable job or not being able to obtain a satisfactory career. Design/methodology/approach: A two-wave study among graduate students currently in an internship investigated these relationships. Data on career-entry worries, perceived employability and an evaluation of the internship were collected from 80 students (mean age: 24.6 years, 68% female) from various fields of study aiming at both bachelor's and master's degrees. Findings: The results showed that positively evaluated internships contributed to graduates' self-perceived employability by means of reduced career-entry worries over an eight-week period. Originality/value: By considering graduates' career-entry worries – the perceived uncertainty about finding an "appropriate" career in the future – the authors introduce a new concept to the career literature and show that these worries are significant in terms of self-assessed employability.